2018
DOI: 10.3390/beverages4010011
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Pivot Profile Variant Using CATA Questions in the Development of a Whey-Based Fermented Beverage

Abstract: Abstract:During the development of a food product, the application of rapid descriptive sensory methodologies is very useful to determine the influence of different variables on the sensory characteristics of the product under development. The Pivot profile (PP) and a variant of the technique that includes check-all-that-apply questions (PP + CATA) were used for the development of a milk drink fermented from demineralised sweet whey. Starting from a base formula of partially demineralised sweet whey and gelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It should be mentioned that the Pivot sample is not usually considered for statistical calculations in current investigations where the PP technique is used for the sensory characterization of foods using this technique (Deneulin et al, 2018;Lelièvre-Desmas et al, 2017;Miraballes et al, 2018;Rios-Mera et al, 2019;Thuillier et al, 2015).…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that the Pivot sample is not usually considered for statistical calculations in current investigations where the PP technique is used for the sensory characterization of foods using this technique (Deneulin et al, 2018;Lelièvre-Desmas et al, 2017;Miraballes et al, 2018;Rios-Mera et al, 2019;Thuillier et al, 2015).…”
Section: Notementioning
confidence: 99%
“…This is why the Pivot technique (Thuillier et al, 2015) can be a suitable tool for the analysis of adulterated food since: it can be carried out with consumers, its execution is easy, it allows the comparison of products (Pivot or reference sample vs. other samples) and the results can be analyzed using different multivariate techniques available in the field of food adulteration such as discriminant analysis (DA), correspondence analysis (CA), among others (Karoui, Mazerolles, Bosset, de Baerdemaeker, & Dufour, 2007). However, in order to use the Pivot technique for adulterated food, it is necessary to per- Miraballes, Hodos, and Gámbaro (2018) and Pearson et al (2020), the Pivot sample is used only to perform the paired comparison of samples without determining their respective intensity values for each attribute, which may be a limitation for the comparison of results. For all the above, the objective of this study was to modify the Pivot sensory technique and determine its suitability for the sensory analysis of adulterated coffees.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers recently published the development of a similar method, called "PP + CATA" or "Pivot-CATA," which they tested with wheybased fermented beverages (Miraballes et al, 2018) and instant black coffee (Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the method provides simple means for categorizing products, without using semantic analyses, which often create biases when performed by non‐specialists. Researchers recently published the development of a similar method, called “PP + CATA” or “Pivot‐CATA,” which they tested with whey‐based fermented beverages (Miraballes et al, 2018) and instant black coffee (Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a correspondence was found between the angular cup and a more bitter taste only for the soft drink. The sweetener sucrose may also be used for other purposes than increasing sweetness [4]. These authors showed that it also affects the texture and creaminess of a new product based on partially demineralized sweet whey and gelatin added to milk powder and cassava starch.…”
mentioning
confidence: 99%